2017
DOI: 10.1371/journal.pone.0174101
|View full text |Cite
|
Sign up to set email alerts
|

The effects of substance P and acetylcholine on human tenocyte proliferation converge mechanistically via TGF-β1

Abstract: Previous in vitro studies on human tendon cells (tenocytes) have demonstrated that the exogenous administration of substance P (SP) and acetylcholine (ACh) independently result in tenocyte proliferation, which is a prominent feature of tendinosis. Interestingly, the possible link between SP and ACh has not yet been explored in human tenocytes. Recent studies in other cell types demonstrate that both SP and ACh independently upregulate TGF-β1 expression via their respective receptors, the neurokinin 1 receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Using in vitro and in vivo experiments, we tested our hypothesis that the duration of SP exposure determines its effect on the tendons. While brief exposure to SP is closely related to tendon healing, repetitive long-term exposure is strongly linked to the development of tendinopathy [ 22 , 23 ]. Our quantification using different histological factors and analysis of varying tendon strengths after injection of SP revealed that SP is a cause of tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Using in vitro and in vivo experiments, we tested our hypothesis that the duration of SP exposure determines its effect on the tendons. While brief exposure to SP is closely related to tendon healing, repetitive long-term exposure is strongly linked to the development of tendinopathy [ 22 , 23 ]. Our quantification using different histological factors and analysis of varying tendon strengths after injection of SP revealed that SP is a cause of tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, an increase in substance P has been reported in SS: this may represent an early element of the fibrotic cascade, since substance P upregulates TGF-β and promotes neo-angiogenesis, fibroblasts proliferation, and contraction, without directly altering ECM synthesis. 12 A myofibroblast-mast cell-neuropeptide axis has been described, in which the interaction of substance P with the resident mast cells in the cellular microenvironment is involved in fibrosis progression. 13 …”
Section: Introductionmentioning
confidence: 99%
“…As early as in 1913, stem used the amniotic membrane for skin burn and ulcer wound transplantation. Subsequently, the amniotic membrane was used in ophthalmology, neurosurgery, and gynaecology as a dressing [1719]. Studies have found that human amniotic membrane cells present the characteristics of embryonic stem cells and are also differentiated into three different types of embryonic cells; amniotic membrane cells show low immunogenicity and immunosuppressive effects and do not induce rejection or tumorigenicity after transplantation.…”
Section: Discussionmentioning
confidence: 99%